Senegal : Early Grade Reading Assessment - Sprenger-Charolles, Liliane (World Bank, Washington, DC, 2013)
In international assessments (Progress in International Reading Literacy Study - Organization for Economic Co-operation and Development [PISA-OECD] and Progress in International Reading Literacy Study International Evaluation of Educational Achievement [PIRLS-IEA]), children's reading skills are not assessed before the fourth grade. For students who are poor readers, it is often too late by this time to carry out efficient and effective remedial instruction. To be efficient remedial instruction should be conducted as early as possible. In addition, most major assessments are only composed of reading comprehension tasks and do not take into account the level of word reading fluency (including accuracy and speed) and listening comprehension. However, research suggests that reading comprehension is associated with capacity in these complementary tasks. The last two analyses indicated that in the two groups (Wolof and French), correlations between socioeconomic status and various tasks were not significant and that socioeconomic status does not contribute to variance in reading skills. This was also the case for phonemic analysis and the knowledge of letter names, although correlations between these tasks and the reading tasks were high. Correlations between the pseudo-word and word reading tasks were very high, and the ability to read pseudo-words was the only skill that explained variance in word reading (isolated or in context). Finally, correlations between reading and listening comprehension were very high, and listening comprehension was the only skill that consistently explained variance in reading comprehension.